2021
DOI: 10.1371/journal.pone.0261414
|View full text |Cite
|
Sign up to set email alerts
|

Women’s experiences of maternal and newborn health care services and support systems in Buikwe District, Uganda: A qualitative study

Abstract: Background Uganda continues to have a high neonatal mortality rate, with 20 deaths per 1000 live births reported in 2018. A measure to reverse this trend is to fully implement the Uganda Clinical Guidelines on care for mothers and newborns during pregnancy, delivery and the postnatal period. This study aimed to describe women’s experiences of maternal and newborn health care services and support systems, focusing on antenatal care, delivery and the postnatal period. Methods We used triangulation of qualitati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 18 publications
(24 reference statements)
1
5
0
1
Order By: Relevance
“…Implications for SBC programming SBC interventions can positively change gender norms and household power dynamics to improve well-being across multiple areas, including family planning and reproductive health. Our study corroborates existing literature on the importance of partner support for contraceptive use (14)(15)(16)(17)(18)(19)(20)23). We show that while men and women mostly want their partners to support them in similar ways, they de ne this support differently.…”
Section: Summary Of Ndingssupporting
confidence: 88%
See 2 more Smart Citations
“…Implications for SBC programming SBC interventions can positively change gender norms and household power dynamics to improve well-being across multiple areas, including family planning and reproductive health. Our study corroborates existing literature on the importance of partner support for contraceptive use (14)(15)(16)(17)(18)(19)(20)23). We show that while men and women mostly want their partners to support them in similar ways, they de ne this support differently.…”
Section: Summary Of Ndingssupporting
confidence: 88%
“…A study conducted in rural Uganda demonstrated that women who found it di cult to have conversations with their partner about reproductive health issues, including family planning, were signi cantly more likely to have symptoms of depression and anxiety compared to women who found these conversations easy (15). Other studies also conducted in Uganda found that the majority of women expressed a general discontent with partner involvement in reproductive health, with many women describing a lack of autonomy in decision-making about their health (16,17). These studies cited nancial dependency, gender disparities, lack of autonomy, poor communication between couples, and perceptions regarding social norms as major challenges to reproductive health service utilization (16,17).…”
Section: Review Of Relevant Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…Long travel time remains a challenge among women in remote areas even where interventions have been implemented [90,98] and has been linked with lack of public transport and roads in poor conditions [89,[99][100][101]. Access to bicycles has shown to be a pro-poor option in increasing access to health centers and can be used as entry point to intervene on areas with poor geographical access [100], supplemented with contracted transporters [77].…”
Section: Discussionmentioning
confidence: 99%
“…Our findings indicate that gaps in pre-service training curricula were consistent across the study countries, with a lack of focus on woman centered care, information sharing and shared decision making, care related to women who experience physical and sexual violence and abuse as well as aspects concerning fundamental human rights when providing midwifery care. These aspects of respectful care have been described as missing in a number of studies despite being seen as very critical in relation to women's experiences during the pregnancy, childbirth and postnatal continuum, as well as important in promoting the use of facility-based maternity care [27][28][29][30][31].…”
Section: Discussionmentioning
confidence: 99%